2011
DOI: 10.1002/hep.24644
|View full text |Cite
|
Sign up to set email alerts
|

Field-practice study of sorafenib therapy for hepatocellular carcinoma: A prospective multicenter study in Italy

Abstract: on behalf of the SOFIA (SOraFenib Italian Assessment) study group A multicenter randomized controlled trial established sorafenib as a standard of care for patients with advanced hepatocellular carcinoma (HCC). Because the study was prematurely interrupted due to survival benefits in the sorafenib arm, we conducted an observational study to adequately assess risks and benefits of this regimen in field practice. Starting in 2008, all clinically compensated patients with advanced HCC and those with an intermedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
293
6
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 329 publications
(336 citation statements)
references
References 31 publications
(52 reference statements)
31
293
6
6
Order By: Relevance
“…The response to sorafenib seems to be variable, and treatment is associated with signifi cant side effects (3)(4)(5)(6)(7)(8). Importantly, there are no clinically applied biomarkers for predicting sorafenib response in HCC ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The response to sorafenib seems to be variable, and treatment is associated with signifi cant side effects (3)(4)(5)(6)(7)(8). Importantly, there are no clinically applied biomarkers for predicting sorafenib response in HCC ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sorafenib is the mainstay of therapy for advanced HCC and the only systemic drug that has shown any survival advantage in HCC so far ( 3,4 ). However, patients' response is modest, and sorafenib treatment is associated with side effects (3)(4)(5)(6)(7)(8). Thus, several studies looked for predictive markers for sorafenib response (9)(10)(11), yet no such biomarkers have entered the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Since approval was granted to sorafenib, physicians have accrued a wealth of experience with the fine-tuning of sorafenib in their daily clinical practice, and several 'real-world' studies have continued to investigate the safety and efficacy of sorafenib. Among them is a multinational postmarketing study, GIDEON, and the Italian field-practice study by the Sorafenib Italian Assessment (SOFIA) study group [7][8][9][10][11], as well as a number of other studies in Europe and North America [12][13][14][15] . These real-world experiences have allowed us to assess sorafenib in patients who are not selected by strict clinical trial criteria but by physician judgment, including patients with comorbidities and those receiving concomitant medication.…”
mentioning
confidence: 99%
“…It is also recommended for patients with intermediate HCC who are unsuitable for treatment with TACE or have TACE-refractory disease [4,24] To our knowledge, no clinical trial in HCC has prospectively compared a different starting dose of sorafenib with the approved dose of 800 mg/day. The SOFIA study reported outcomes for patients who maintained an initial dose of 800 mg/day and for patients in whom the initial dose was reduced in order to manage AEs [9]. In a retrospective analysis, the authors reported a median overall survival (OS) of 21.6 months for patients who received 400 mg/day of sorafenib for 70% of the treatment period and 9.6 months for those who maintained full dosing or had a dose reduction for <70% of the treatment period.…”
mentioning
confidence: 99%
See 1 more Smart Citation